Sepsis in Internal Medicine: blood culture-based subtypes, hospital outcomes, and predictive biomarkers - Zizzo, Gaetano; Guazzardi, Gabriele; Bompane, Daniela; Di Terlizzi, Francesco; Rotola, Giorgio; Stefani, Ilario; Medugno, Michela; Bucalo, Mario; Mazzone, Antonino (Frontiers in Medicine, 2025)
BackgroundSepsis is a challenging condition increasingly managed in medical wards, however literature and clinical evidence in this hospital setting are lacking.MethodsUsing the computational i2b2 framework, we retrospectively analyzed data from patients admitted to internal medicine units of four hospitals in Lombardy (Italy) between January 2012 and December 2023, with a discharge diagnosis of sepsis, septic shock, or septicemia.ResultsA total of 4,375 patients were recruited. Median length of stay (LOS) was 14 days, and mean ward-to-intensive care unit (ICU) transfer and in-hospital mortality rates were 11 and 26%, respectively; significant differences were observed over the years, with LOS peaks preceding mortality peaks by 1 year. Blood culture-negative sepses showed shorter stays and higher mortality (acute kidney injury and fast deterioration) compared to culture-positive ones; polymicrobial sepses showed higher ICU transfer rates (acute respiratory distress); while multidrug-resistant (MDR+) and/or polymicrobial sepses showed longer stays and higher mortality (complicated course) compared to drug-sensitive or monomicrobial ones. C-reactive protein elevation predicted rapidly evolving culture-negative sepsis, whereas lower leukocyte counts predicted prolonged hospitalization; higher fractions of inspired oxygen predicted polymicrobial sepsis, while lactate elevation predicted ICU transfer; ferritin elevation and increased leukocyte counts predicted MDR+ sepsis, while further ferritin elevation and decreased platelet counts predicted death. From 2016 to 2023, MDR+ sepsis frequency declined, due to decreased resistance to several antibiotic classes, such as cephalosporins, fluoroquinolones, and aminoglycosides; however, carbapenemase- and extended-spectrum beta-lactamase-producing Gram-negative bacteria, as well as vancomycin-resistant enterococci, increased, as did the frequency of polymicrobial sepsis following the COVID-19 outbreak.ConclusionThis work provides novel insights into sepsis management in internal medicine units, highlighting the need for validated biomarkers and implemented therapies in this scenario.